Peningkatan Pemahaman Mengenai Menstruasi Melalui Penyuluhan Serta Pemeriksaan Golongan Darah Di Usia Dini - Sukmawati Syarif; A. Muflihunna; Zainal Abidin; Masdiana Tahir (IAI Darussalam, 2020)
Menstruation is a physiological change in a woman's body that occurs periodically and is influenced by reproductive hormones either FSH-Estrogen or LH-Progesterone. In women, this usually occurs every month between teens to menopause, and lasts around 7-28 days. Knowing the characteristics of menstruation early is a very important thing to know because it is an early learning about the reproductive system and their health. Blood type is an inherited antigen on the surface of red blood cells. The two most important types of blood classification to know are the classification of ABO and Rhesus (Rh factor). Blood type examination is an activity that is sometimes overlooked by the community, in this case the needs of the Blood Type are carried out for clinical purposes such as: blood transfusions, preventing transfusion complications, and for pregnant women. According to empirical data obtained in 2017 the level of understanding of menstruation and blood type in primary schools is very low. For this reason, efforts are made to provide education and information as well as checks on children from an early age as a starting point for character building in improving education and knowledge in general and specifically regarding health